Saline effect of different heavy metal accumulation of pb and Zn in shells of blood (anadara granosa) - Dharma Eka Putra; Yusni Ikhwan Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Accumulation of Pb and Zn in Blood Shells can be seen that the Shellfish not respond toheavy metal that accumulates in the body at different salinity. Evaluation of the abilityaccumulation Shellfish Blood (Anadara granosa) against Pb fluctuated. While metals Zn showeda fairly high response in the process of accumulation of heavy metals in blood Shells.The concentration of Pb at 20 ppm salinity treatments were the highest found in bothreplicates with a concentration of 0.05 ppm which is equal to 0036 mg / g. While the data waslowest for the first repeat also with a concentration of 0.05 ppm was 0.0027 mg / g. While theconcentration of Zn in the treatment of 20 ppm the highest salinity found in both replicates witha concentration of 2 ppm which is equal to 0.86 mg / g. While the Zn concentration was lowestfor the second replay with 1.5 ppm concentration of 0.38 mg / g.Water quality at each research station there was no difference so far. However, waterquality in the study site contained a water quality to support shellfish life blood. Initialtemperature in this study is the final temperature is 290C and 280C.Keywords: Heavy Metal, Anadara granosa, Salinity